MAKNA DAN PENGGUNAAN –MAI (STUDI TENTANG MODALITAS BAHASA JEPANG) - Talmera, Hidayat; Aibonotika, Arza; Isnaini, Zuli Laili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study will discus about the meaning and using of the modal auxilarry –mai. This research were taken from a book titled chuujyoukyuu nihongo hatsugen bunkei and www.kotonoha.gr.jp/shonagon/. The method that were used is descriptive method based on the thoery about epistemic and intentional modality. The data were analyzed using replacement technique. From the result of the analysis, it is conclude that –mai could express a negative decision and negative prediction. Base on that, the modal auxillary –mai could be clssified into epistemic and intensional modality.Keywords: Epistemic Modality, Intensional Modality,Prediction.